2015
DOI: 10.1002/em.21944
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage foci: Meaning and significance

Abstract: The discovery of DNA damage response proteins such as γH2AX, ATM, 53BP1, RAD51, and the MRE11/RAD50/NBS1 complex, that accumulate and/or are modified in the vicinity of a chromosomal DNA double-strand break to form microscopically visible, subnuclear foci, has revolutionized the detection of these lesions and has enabled studies of the cellular machinery that contributes to their repair. Double-strand breaks are induced directly by a number of physical and chemical agents, including ionizing radiation and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
236
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(245 citation statements)
references
References 179 publications
(218 reference statements)
5
236
1
3
Order By: Relevance
“…the dicentric assay (Romm et al 2014). However, this is much less of an issue for the gamma-H2AX assay where, in comparison, there are many events (foci) per cell and many other factors contributing to dose uncertainty (Rothkamm & Horn 2009;Rothkamm et al 2015). In addition, no significant effect of post-exposure time on the dose estimate was seen, as found in the first inter-comparison.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…the dicentric assay (Romm et al 2014). However, this is much less of an issue for the gamma-H2AX assay where, in comparison, there are many events (foci) per cell and many other factors contributing to dose uncertainty (Rothkamm & Horn 2009;Rothkamm et al 2015). In addition, no significant effect of post-exposure time on the dose estimate was seen, as found in the first inter-comparison.…”
Section: Discussionmentioning
confidence: 64%
“…To improve dose estimates, however, there are a number of additional points that will need to be addressed going forward, before all the influencing factors are fully understood and the assay can be categorized as fully operational for routine dose estimation. This includes the variability between individual slides (staining reproducibility) and variability between images (image/microscope setting reproducibility) (Rothkamm & Horn 2009;Rothkamm et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is somewhat puzzling since most studies report a robust correlation between RAD51 and γH2A.X nuclear foci formation. Nonetheless, the exact nature, meaning and significance of DNA repair proteins nuclear foci remain unclear 45 , and the RAD51 nuclear foci observed in PALB2 T413S expressing cells do not necessarily reflect regular HDR events. It is conceivable that, through its interaction with BRCA1, PALB2 T413S can initiate RAD51 recruitment, but for as-yet-unknown reasons, fail to promote HDR.…”
Section: Discussionmentioning
confidence: 99%
“…53BP1 is a nuclear protein that rapidly localizes to sites of DNA double-strand breaks and activates p53 along with other kinases, which plays critical roles in DDRs including cell cycle arrest, DNA repair, and apoptosis [18][19][20]. It has been well documented in vitro by immunofluorescence studies that 53BP1 exhibits faint diffuse nuclear staining in untreated primary cells, whereas after exposure to radiation, 53BP1 is localized at the sites of DNA double-strand breaks and forms discrete nuclear foci [20,21]. We have recently demonstrated that the presence of 53BP1 nuclear foci as detected by immunofluorescence might serve as a valuable molecular marker of genomic instability during carcinogenesis, which seems to be induced at the precancerous stage during thyroid, skin and cervical carcinogenesis, as follicular adenoma and actinic keratosis [22,23].…”
Section: Thyroid Tissuesmentioning
confidence: 99%